Nurse's role in the management of medical and hospital equipment (Research, Society and Development, 2022)
The management of medical-hospital equipment starts from the acquisition forecast to its use, which makes the process meticulous. Material resources in health can be classified according to several criteria: purpose, storage specificity, value and level of criticality or application. The nurse's work in coordination positions has been noted for enabling, encouraging and creating technical conditions for the assistance to be properly developed. The objective of describing the role of nurses in the management of medical-hospital technologies. The methodology used was a bibliographic review in the Google Scholar database, BVS and SciELO, published between 2012 and 2021, available in full. Initially, 71 studies were found and after applying the filters, according to the inclusion and exclusion criteria, 56 studies were eliminated. Duplicate studies, monographs, handouts and books were not considered. At the end, 15 scientific articles were included. The management of hospital equipment is part of care management; therefore, it is the nurse's responsibility to ensure that their team is properly trained and that the equipment used in patients works properly. The role of planning and controlling medical and hospital equipment is the nurse's, which is linked. Therefore, it is essential in the management of equipment that it is worked towards quality and productivity, which makes it possible to reduce costs.